The Analysis of Transnational Organized Crime/Tnoc Threats and Risk Analysis Pre-And Post-Covid-19 Pandemic Occurred in Indonesia - Ilmawan, Irfianto Udhi; Runturambi, Arthur Josias Simon (Budapest International Research and Critics University, 2022)
This article tries to analyze the threats and risks of Transnational Organized Crime (TNOC) that occurred during the pandemic, especially in the smuggling of narcotics, psychotropics, and precursors (NPP). The closure of borders between countries due to the prevention of the spread of the Covid-19 virus, directly reduces the findings/actions of violations at the Indonesian border. Using a qualitative approach by analyzing data from the literature and documents related to TNOC. This article aims to analyze the data, so that the reduction in the number of prosecutions at the border does not cause bias in interpretation in concluding the threat of TNOC (narcotics). Did TNOC really decrease during the pandemic, or did it just change shape/mode. The results showed that there was no impact of the Covid-19 pandemic on TNOC activities in the circulation of NPP. The data found indicate that there is an equally large threat and risk from TNOC in Indonesia. The impact of the Covid-19 pandemic on TNOC's activities is only in changing the modus operandi of smuggling NPP into Indonesia.